Characteristics of Pediatric Patients with Typhoid Fever in Makassar - Mufidah; Najamuddin Andi Palancoi; Utami Murti Pratiwi (Jurnal Multidisiplin Madani, 2022)
Typhoid fever is an endemic disease that causes 21 million cases and 222,000 of them die each year. Research objective: to know the characteristics of pediatric patients with typhoid fever at Laburan Baji General Hospital, Makassar. The research population was 61 with 23 research samples. This research is analytic and quantitative with a cross-sectional study design. The sampling technique is purposive sampling. Data analysis used IBM SPSS Statistics 23 software. The results showed that the largest sample was boys, amounting to 17 (73.9%) aged 1-9 years. The highest levels of O and H titers were 1/320 in boys. The conclusion of this study is that the highest incidence of typhoid fever is found in boys aged 1-9 years compared to girls with an O and H titer level of 1/320